The Belsey Mark IV: an operation with an enduring role in the management of complicated hiatal hernia - Markakis, Charalampos (BioMed Central, 2013)
BACKGROUND: The Belsey Mark IV operation has been used for the management of hiatal hernia for over 40 years, but with the introduction of laparoscopic techniques its role has become questionable. To determine the current role of this procedure we present a contemporary series of patients. METHODS: We reviewed fifteen consecutive patients, mean age of 63 years, who underwent a Belsey Mark IV fundoplication for gastroesophageal reflux in the presence of a hiatal hernia in our Department from January 2005 to March 2011. Indications for the thoracic approach included paraesophageal hernias, recurrent hiatal hernias and previous upper abdominal surgery. RESULTS: There was no operative mortality. Immediate postoperative morbidity included 1 case of bleeding, 1 case of pneumonia and 1 case of atrial fibrillation. The mean length of stay was 5.9 days. After a mean follow-up time of 49 months, all patients reported total or partial alleviation of their symptoms. No hernia recurrence was detected during barium swallow examination. CONCLUSIONS: The Belsey approach is a procedure that can be useful as an alternative in selected cases when there are co-morbidities complicating the transabdominal (laparoscopic) approach.